2023
DOI: 10.47115/bsagriculture.1216576
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Region on Nut and Biochemical Traits of Mincane Hazelnut Cultivar

Abstract: In this study investigated the effect of region on the nut and biochemical traits in Mincane hazelnut cultivar. The study was carried out in the Trabzon (Black Sea Region) and Sakarya (Marmara Region) districts, in 2021 and 2022. The material of the study consisted of the nut of Mincane hazelnut cultivar grown in both regions. Depending on regions, nut weight was determined from 1.89 (Black Sea) to 2.14 g (Marmara), while kernel weight was found from 1.89 (Black Sea) to 2.14 g (Marmara). The highest total phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…According to the kernel size, the total phenolics were determined between 759 mg 100 g -1 (medium) and 819 mg 100 g -1 (large) in the study. In Kalınkara hazelnut cultivar, the total phenolics were determined to be 1006 mg 100 g -1 (Göncüoğlu- Taş and Gökmen, 2015), 436.5 mg 100 g -1 (Balık, 2021), 709 mg 100 g -1 -1181 mg 100 g -1 (Karakaya, 2021), and between 783 -1098 mg 100 g -1 (Karakaya, 2023). In general, the results obtained from the study in terms of total phenolics were found to be compatible with other studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the kernel size, the total phenolics were determined between 759 mg 100 g -1 (medium) and 819 mg 100 g -1 (large) in the study. In Kalınkara hazelnut cultivar, the total phenolics were determined to be 1006 mg 100 g -1 (Göncüoğlu- Taş and Gökmen, 2015), 436.5 mg 100 g -1 (Balık, 2021), 709 mg 100 g -1 -1181 mg 100 g -1 (Karakaya, 2021), and between 783 -1098 mg 100 g -1 (Karakaya, 2023). In general, the results obtained from the study in terms of total phenolics were found to be compatible with other studies.…”
Section: Resultsmentioning
confidence: 99%
“…The total flavonoids were determined between 8.2 mg 100 g -1 (medium) and 8.7 mg 100 g -1 (small). In Kalınkara hazelnut cultivar, the total flavonoids were determined to be 12.59 mg 100 g -1 (Balık, 2021), 5.07 mg 100 g -1 (Göncüoğlu-Taş and Gökmen, 2015), 5.8 mg 100 g -1 -10.6 mg 100 g -1 (Karakaya, 2021), and between 7.5 mg 100 g -1 -11.5 mg 100 g -1 (Karakaya, 2023). It can be said that the results obtained from other studies in terms of total flavonoids were similar to this study's results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation